2015
DOI: 10.1111/josh.12290
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Cyberbullying and School Bullying Victimization in a Regional Census of High School Students, 2006‐2012

Abstract: Despite decreases in school bullying, cyberbullying rose steadily, particularly among girls. Increased attention to sociodemographic differences in bullying could promote help-seeking and positive online behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
83
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 33 publications
(42 reference statements)
6
83
1
3
Order By: Relevance
“…For example, cyberbullying may have increased more dramatically among girls than boys. 24 As compared with adolescent boys, adolescent girls also now use mobile phones with texting applications more frequently and intensively 25 and problematic mobile phone use among young people has been linked to depressed mood. 26 Interestingly, the sex differences in trends were not consistent across age groups, as the prevalence of depression followed similar temporal trends in young men and women.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cyberbullying may have increased more dramatically among girls than boys. 24 As compared with adolescent boys, adolescent girls also now use mobile phones with texting applications more frequently and intensively 25 and problematic mobile phone use among young people has been linked to depressed mood. 26 Interestingly, the sex differences in trends were not consistent across age groups, as the prevalence of depression followed similar temporal trends in young men and women.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in the most recent wave of a national online survey, LGBT youth reported lower rates of school verbal and physical harassment than they had in previous waves (Kosciw, Greytak, Palmer, & Boesen, 2014). Also, a recent regional study found that sexual minority youth, like their heterosexual counterparts, experienced a decline in school bullying victimization (Kessel Schneider et al, 2015). Whether or not such positive trends hold true in a more broadly representative sample of adolescents, whether trends occur equally for males and females, and whether sexual orientation disparities have narrowed or disappeared are critical issues to examine.…”
Section: Two Decades Of Changementioning
confidence: 99%
“…Perlus and colleagues, analyzing waves of a national survey of 6 th through 10 th grade students, found that physical fighting and in-school bullying victimization both declined significantly from 1998 to 2010, though when genders were analyzed separately, results for being bullied were significant only for boys (Perlus, BrooksRussell, Wang & Iannotti, 2014). Similarly, a set of regional high school surveys found a decrease in bullying victimization from 2006 to 2012, with that change driven by a significant drop in the bullying of males but not females (Kessel Schneider, O'Donnell, & Smith, 2015).…”
Section: Two Decades Of Changementioning
confidence: 99%
“…Diversos factores han contribuido para ello: facilidad de ocultar la identidad, estar en contacto con la víctima, practicar violaciones o agresiones de la intimidad (Kowalski et al, 2014). Tomando como referencia los datos obtenidos en esta investigación, las TIC se han convertido en un medio adicional para extender el acoso escolar a otros medios y esferas, pues los datos obtenidos en este estudio ponen de manifiesto que el 75% de los alumnos que son víctimas de acoso cibernético también lo son en el contexto escolar, hecho que avalan las investigaciones de Andrade (2012), Coelho et al (2016), Kessel Schneider et al (2015), Kowalski et al (201 0, 2014) Garaigordobil Gaspar, M., Simões, C., Tomé, G., Camacho, I., Ferreira, M., Ramiro, L., Reis, M., Gaspar, T., Veloso, S., Loureiro, N., Borges, A., Alves, J. & Equipa Aventura Social (2012 Giménez Gualdo, A. M., Hunter, S. C., Durkin, K., Arnaiz, P., & Maquilón, J. J.…”
Section: Discusión Y Conclusionesunclassified
“…Dentro de las diferentes tipologías y manifestaciones del cyberbullying (Kessel Schneider, O'Donnell, & Smith, 2015;Kowalski, Agatston, & Limber, 2010;Lucas Molina et al, 2016;Meter & Bauman, 2015) señalamos las siguientes:…”
unclassified